2018
DOI: 10.3389/fphar.2018.00122
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Polyphenols in Cardiac Fibrosis

Abstract: Cardiac fibrosis, in response to injury and stress, is central to a broad constellation of cardiovascular diseases. Fibrosis decreases myocardial wall compliance due to extracellular matrix (ECM) accumulation, leading to impaired systolic and diastolic function and causing arrhythmogenesis. Although some conventional drugs, such as β-blockers and renin-angiotensin-aldosterone system (RAAS) inhibitors, have been shown to alleviate cardiac fibrosis in clinical trials, these traditional therapies do not tend to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 148 publications
(151 reference statements)
1
32
0
1
Order By: Relevance
“…DOX also interferes with iron regulation [ 24 ], up-regulates NF-κB expression, which consequently causes the release of pro-inflammatory cytokines, i.e., tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6), and triggers vascular and cardiac inflammatory reaction [ 25 ] and exaggerates their downstream apoptotic pathways [ 26 ]. In addition, oxidative stress activates several pro-fibrogenic factors, which enhances the accumulation of extracellular matrix and development of cardiac fibrosis [ 27 ], remodeling [ 28 ], and eventual cardiac dysfunction [ 29 ]. DOX is still in use.…”
Section: Introductionmentioning
confidence: 99%
“…DOX also interferes with iron regulation [ 24 ], up-regulates NF-κB expression, which consequently causes the release of pro-inflammatory cytokines, i.e., tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6), and triggers vascular and cardiac inflammatory reaction [ 25 ] and exaggerates their downstream apoptotic pathways [ 26 ]. In addition, oxidative stress activates several pro-fibrogenic factors, which enhances the accumulation of extracellular matrix and development of cardiac fibrosis [ 27 ], remodeling [ 28 ], and eventual cardiac dysfunction [ 29 ]. DOX is still in use.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have reported that ISO, a flavonol, alleviates hepatic fibrosis in NASH model mice (Ganbold et al, 2019). Although several flavonols have been reported to improve cardiac dysfunction and fibrosis (Suzuki et al, 2007;Li et al, 2013;Geetha et al, 2014;Guo et al, 2015;Zhang et al, 2018), very little is known about the effect of ISO on cardiac hypertrophy and fibrosis. Microarray analysis of ISO-treated hAESCs revealed that ISO has strong antifibrotic effects as well as anti-inflammatory and antioxidative functions.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the β-adrenergic nervous system and RAAS has been commonly found in fibrotic HF patients, and β-blockers and RAAS inhibitors have been suggested as a first-line treatment to correct the underlying cardiac dysfunction and reduce morbidity [7,118]. The overstimulation of β-adrenoceptor may result in the impairment of the negative modulation of H 2 S on the β-adrenoceptor system, resulting in a calcium overload, leading to the impairment of cardiac contractility and, ultimately, to cardiomyocyte death [119].…”
Section: Neurohormonal Overstimulationmentioning
confidence: 99%